Education in Colombia: an Approach for Competences and “Glocation” (Papeles, 2018)
In the dichotomy between universals and localisms, hegemonic Western Eurocentric culture has now reached its limits. In this context, and given the fact that we cannot think of one global cultural pattern to which all plural forms of culture can belong, the need arises to educate towards these proposed foreign universals in the same way as local knowledge. The particular approach of competencies adopted and promoted by the Colombian National Ministry of Education has begun to cautiously harmonizethese extremes of globalness and localness.
Keywords: hegemonic; Western Eurocentric culture; hegemonic; universals